Nano wear particles and the periprosthetic microenvironment in aseptic loosening induced osteolysis following joint arthroplasty - Xie, Yu; Peng, Yujie; Fu, Guangtao; Jin, Jiewen; Wang, Shuai; Li, Mengyuan; Zheng, Qiujian; Lyu, Feng-Juan; Deng, Zhantao; Ma, Yuanchen (Frontiers in Cellular and Infection Microbiology, 2023)
Joint arthroplasty is an option for end-stage septic arthritis due to joint infection after effective control of infection. However, complications such as osteolysis and aseptic loosening can arise afterwards due to wear and tear caused by high joint activity after surgery, necessitating joint revision. Some studies on tissue pathology after prosthesis implantation have identified various cell populations involved in the process. However, these studies have often overlooked the complexity of the altered periprosthetic microenvironment, especially the role of nano wear particles in the etiology of osteolysis and aseptic loosening. To address this gap, we propose the concept of the "prosthetic microenvironment". In this perspective, we first summarize the histological changes in the periprosthetic tissue from prosthetic implantation to aseptic loosening, then analyze the cellular components in the periprosthetic microenvironment post prosthetic implantation. We further elucidate the interactions among cells within periprosthetic tissues, and display the impact of wear particles on the disturbed periprosthetic microenvironments. Moreover, we explore the origins of disease states arising from imbalances in the homeostasis of the periprosthetic microenvironment. The aim of this review is to summarize the role of relevant factors in the microenvironment of the 2 This is a provisional file, not the final typeset article periprosthetic tissues, in an attempt to contribute to the development of innovative treatments to manage this common complication of joint replacement surgery.